HOW ESG SCORES INFLUENCE COST OF EQUITY AND ENTERPRISE VALUE: INSIGHTS FROM A SINGLE-FIRM STUDY (Lex localis - Journal of Local Self-Government, 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) Scores on a firm’s cost of equity and enterprise value. Following regulatory requirements for publishing the Business Responsibility and Sustainability Report (BRSR) together with annual reports, Indian companies have increased transparency in ESG disclosures. Such disclosure enables investors and regulators to better evaluate sustainability practices and associated financial risks. An empirical case study of Swaraj Engines Ltd over 2019–20 to 2023–24 applies the Capital Asset Pricing Model (CAPM), Multiple Regression Analysis, Granger Causality, and Vector Auto Regression (VAR) to assess ESG impacts on financial parameters. Results indicate that effective ESG practices contribute to lower cost of equity and higher firm value, highlighting the importance of sustainability integration in corporate financial management.